Constructing ethical learning spaces through interdisciplinary dialogue - Dawson, Leslie; Robinson, Jack (My University, 2021)
First piloted in 2017, MacEwan University’s Interdisciplinary Dialogue is a collaborative teaching and learning project that addresses topics relating to social justice across disciplines. In 2019, in collaboration with kihêw waciston Indigenous Centre, the Dialogue expanded its intercultural learning through a partnership with University nuhelot’įne thaiyots’į nistameyimâkanak Blue Quills and explored truth and reconciliation through a focus on Indigenous research. Building on Willie Ermine’s concept of ‘ethical spaces’, this article highlights how ethical learning spaces were created through Indigenous-led educational forums followed by an online student Interdisciplinary Dialogue. The Dialogue positioned students to explore histories of colonial relationships and their attendant harmful research practices; and to centre Indigenous knowledges and methodologies as foundational to Indigenous research. Students questioned oppressions in western pedagogy, and they envisioned a pedagogy of mutual respect for Indigenous and non-Indigenous ways of knowing. This article focuses on the online discussions conducted by students in the 2019 Dialogue. It shows how students understood that they were participants in disrupting colonial discourse in academia, reframing education for reconciliation, and expanding the construction of ‘ethical spaces’ across the University and beyond.
Keywords: ethical space; ethical learning spaces; Indigenous knowledges; Indigenous research; reconciliation